Khả năng tiếp cận học liệu quốc tế của sinh viên ngành Giáo dục mầm non, Trường Đại học Thủ đô Hà Nội: Thực trạng và giải pháp - Dương, Thảo (Tạp chí Giáo dục, 2026)
In the context of international integration and digital transformation in education, developing the competence to access international learning resources has become an essential requirement for Early Childhood Education students to enhance learning quality, research competence, and teacher preparation. This study employed a theoretical research approach combined with a questionnaire survey of 160 students at Hanoi Metropolitan University to examine the current situation of accessing and using international learning resources among Early Childhood Education students. It also analyzed the difficulties encountered by students, identified their support needs, and proposed several measures to improve their access to international learning resources. The findings indicate that students use international learning resources infrequently and face considerable challenges, particularly in English for academic purposes, as well as in searching for and evaluating information sources. Nevertheless, most students demonstrated positive attitudes and expressed a strong demand for support in improving their ability to access and utilize international learning resources. The findings highlight the necessity of strengthening students’ competence to access international learning resources and provide practical evidence for teacher education institutions to develop strategies that promote the effective integration of international learning resources into teaching and learning.